2009
DOI: 10.1370/afm.961
|View full text |Cite
|
Sign up to set email alerts
|

Management of Test Results in Family Medicine Offices

Abstract: PURPOSE We wanted to explore test results management systems in family medicine offi ces and to delineate the components of quality in results management.METHODS Using a multimethod protocol, we intensively studied 4 purposefully chosen family medicine offi ces using observations, interviews, and surveys. Data analysis consisted of iterative qualitative analysis, descriptive frequencies, and individual case studies, followed by a comparative case analysis. We assessed the quality of results management at each … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
68
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(68 citation statements)
references
References 34 publications
0
68
0
Order By: Relevance
“…As a consequence, there is significant potential for mistakes throughout the process, from ordering and implementing tests, to relaying results to clinicians and notifying patients. 2 Over the past decade, research undertaken predominantly in the US has recognised growing concerns among physicians in general practice about testing and result management, including the lack of defined administrative procedures and the frequency of delays in the process. 4,5 Recommendations have begun to emerge, outlining areas where the process can be improved and standardised.…”
Section: -3mentioning
confidence: 99%
“…As a consequence, there is significant potential for mistakes throughout the process, from ordering and implementing tests, to relaying results to clinicians and notifying patients. 2 Over the past decade, research undertaken predominantly in the US has recognised growing concerns among physicians in general practice about testing and result management, including the lack of defined administrative procedures and the frequency of delays in the process. 4,5 Recommendations have begun to emerge, outlining areas where the process can be improved and standardised.…”
Section: -3mentioning
confidence: 99%
“…First, some practices demonstrated a complete lack of a process for ordering, implementing, and reporting laboratory results. Elder et al 24 observed 2 primary care practices that had no written protocols or procedures for any results management steps. Similarly, Pace et al 25 also determined that a total lack of a process system was associated with laboratory errors and a frequent contributor to patient harm.…”
Section: Breakdowns or Failures In Processmentioning
confidence: 99%
“…Hickner et al 27 reported that errors in laboratory test implementation were nearly double for minority groups compared with Breakdowns in process [24][25][26][27][28][29][30] Practice protocols should include an outlined procedure for laboratory test ordering, reporting of results, and patient notification. Delays in diagnosis 12,25,27,31 Laboratory results should be communicated to patients within 1 business day of receipt by the practice.…”
Section: Influence Of Minorities and Language Barriersmentioning
confidence: 99%
See 1 more Smart Citation
“…3,4 In a qualitative analysis, Elder et al studied the management of test results in 4 separate practices. 5 They note wide variability in the establishment of, and adherence to, systems for results management. Even so, they identify safety awareness and technological adoption as themes that may guide practices in assessing processes for results management.…”
Section: Patient-and Practice-level Strategiesmentioning
confidence: 99%